INTERNATIONAL EXPERIENCES ON USE OF INNOVATIVE MARKETING STRATEGIES OF COMMERCIAL BANKS (Marketing Journal, 2026)
This study conducted a systematic analysis of international experience in the use of innovative marketing strategies in the activities of commercial banks under the conditions of the digital economy. The research examined the practices of leading banks fro m the United States, Europe, and the Asia -Pacific region, focusing on the application of artificial intelligence, mobile banking, social media marketing, and hyper -personalization. The findings demonstrated that digital transformation № 1 -SON YANVA R, 202 6-YIL 346 contributed to strengthening bank –customer relationships, improving service quality, and enhancing overall competitiveness. International experience confirmed that the adoption of innovative marketing technologies had a positive impact on customer experien ce development and supported the formation of long -term customer loyalty in the banking sector.
Keywords: digital banking; innovative marketing; artificial intelligence; mobile banking; fintech; hyper -personalization; customer experience